2018
DOI: 10.1002/joc.5961
|View full text |Cite
|
Sign up to set email alerts
|

How does sub‐hourly rainfall intermittency bias the climatology of hourly and daily rainfalls? Examples from arid and wet tropical Australia

Abstract: Statistical rainfall climatologies for application to problems in ecohydrology or urban flood hydrology employ indices such the average rainfall depth per rain day or rain hour, and the average daily or hourly rainfall intensity. These subsume finetemporal-scale aspects of rainfall arrival such as sub-hourly intermittency that vary among locations with different climatic conditions. Rainfall duration and intensity derived from data aggregated to hourly or daily level thus involve some bias, generally overestim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The same amount of precipitation spread over different time periods will affect many land surface processes [19], such as the amount of precipitation absorbed by the soil, converted to runoff, and re-evaporated by the atmosphere, all of which are important considerations in hydrological modelling and climate modelling in general. Future changes in the intermittency of rainfall may be masked at hourly timescales, leading to flawed estimates of changes in precipitation intensities and their impacts [24]. Identifying shortcomings in the character of modelled subhourly precipitation is thus important for ongoing CPM development.…”
Section: Introductionmentioning
confidence: 99%
“…The same amount of precipitation spread over different time periods will affect many land surface processes [19], such as the amount of precipitation absorbed by the soil, converted to runoff, and re-evaporated by the atmosphere, all of which are important considerations in hydrological modelling and climate modelling in general. Future changes in the intermittency of rainfall may be masked at hourly timescales, leading to flawed estimates of changes in precipitation intensities and their impacts [24]. Identifying shortcomings in the character of modelled subhourly precipitation is thus important for ongoing CPM development.…”
Section: Introductionmentioning
confidence: 99%
“…One example found herein was the rainfall intensity and associated kinetic energy as a crucial variable leading to sediment detachment. During a rainstorm event, rainfall intensity changes several times [128], but daily aggregates, or maximum 30-, 15-, or 6-min intensities are used to calculate rainfall energy in soil erosion models, while more fine-scale data on intensity variability are not available.…”
Section: Common Challenges For Research and Management Of Leverage Armentioning
confidence: 99%
“…In our continuously changing world, sediment management is likely to fail if it continues to target long-term mean values rather than variability. Sediment management might fall behind ongoing and future environmental trends if it continues to omit in the most influential factors and their compound effects [128,136]. Eco-hydrological hindcast modeling for water and sediment management [87,88] provides a step forward for addressing management challenges related to ongoing change.…”
Section: Common Challenges For Research and Management Of Leverage Armentioning
confidence: 99%
“…The It has to be remembered that rain hours typically contain some rainless time. Elsewhere, the author [15] has reported that afternoon rainfall tends to exhibit higher intermittency, which reaches a minimum during the early morning intensity peak. Therefore, true intensities in the afternoon are higher than suggested by the data of Figure 5.…”
Section: The 5-min and Unaggregated Itt Intensity Data: Full Period Omentioning
confidence: 99%
“…This index is simply the total rainfall depth over a period such as a month or a year, divided by the number of rain days in that period; it is therefore the mean wet day rainfall. This is perhaps more correctly described as a measure of the wetness of rain days, and can only be loosely connected with the actual intensity when raining, since rain commonly falls for only a part of each rain day [14,15]. Locations with different degrees of rainfall intermittency (or different variance of rainday intensities) may exhibit different intensities when raining, even if their SDII values are the same.…”
Section: Introductionmentioning
confidence: 99%